ANALISIS ANGGARAN BIAYA KESELAMATAN DAN KESEHATAN KERJA PROYEK KONSTRUKSI GEDUNG SMA N 2 ABIANSEMAL - Ni Kadek Sri Ebtha Yuni; Ni Putu Indah Yuliana (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
One of the efforts made by construction service companies to minimize accident rates is to implement an occupational safety and health management system (OSHMS) for construction. The construction service provider must provide costs for OSH requirements taken from the total project cost. This research has a certain purpose that is to find out the amount of occupational safety and health costs needed as well as the comparison between regulations and the field. The study was conducted in the form of surveys and interviews where the data analysis stage is to compile a list of risks that occur, risk assessment, risk mitigation, calculate OSH costs with the price of the store survey and SE No. 11/SE/M/2019 (SE19) prices and calculate the percentage of OSH costs to the contract. The results showed 22 accident and safety risks identified with 14 low category risks and 8 medium category risks. The OSH cost required based on the price of the field unit is IDR. 402,142,520.00, while the fee based on SE19 is IDR. 359,005,000.00. The OSH costs field prices are greater than OSH costs SE19 with a difference of 0.08% or IDR. 43,137,520.00.